A Cross-over Pharmacokinetic Study of a Double Viral Inactivated Factor IX Concentrate (15 nm Filtration and SD) Compared to a SD Factor IX Concentrate - Goudemand, Jenny; Peynet, Jocelyne; Chambost, Hervé; Négrier, Claude; Briquel, Marie Elisabeth; Claeyssens, Ségolène; Derlon-Borel, Annie; Guérois, Claude; Caron, Claudine; Scherrmann, Jean Michel; Debray, Marcel; Bridey, Françoise (Thrombosis and Haemostasis, 1998)
A double blind randomized cross-over multi-center study has been conducted to compare the pharmacokinetic and coagulation activation markers of high-purity factor IX concentrate subjected to both solvent/ detergent (SD) treatment and 15 nm-filtration (FIX-SD-15) with the licensed product subjected only to solvent-detergent (FIX-SD). This filtration process allows the elimination of small particles, such as non-enveloped viruses (i.e., hepatitis A and parvovirus B19). Eleven severe hemophilia B patients (FIX coagulant activity <2 IU/dl) received one infusion of 60 IU/kg of FIX-SD and one infusion of 60 IU/kg of FIX-SD-15 at least at 10 days interval. Blood samples were obtained before and at various time up to 72 h after infusion. The decay curves of factor IX (FIX:C and FIX:Ag) were evaluated by a model independent method. Bioequivalence was found between the two concentrates using the Schuirmann test. The mean FIX:C and FIX:Ag recovery of FIX-SD-15 was 1.08 and 0.89 IU/dl/IU/kg respectively with a mean half-life of 33.3 h for FIX:C and 25.6 h for FIX:Ag. Six months after initial enrollment, pharmacokinetic parameters were similar in the 7 patients tested. There was no significant variation of prothrombin fragment 1+2 and thrombin-antithrombin complexes measured up to 6 h after infusion, indicating that there was no activation process after administration of FIX. In conclusion, these data demonstrate that the introduction of a 15 nm filtration does not alter the pharmacokinetic profile of a well characterized SD FIX concentrate while providing additional viral safety.